Niche differentiation in savannas : exploring competition-based hypotheses for inter-life form coexistence - Verweij, Richard J T (Department of Biological Sciences, 2015)
Competition-based models predict that coexistence of trees and grasses in savannas may be possible if trees and grasses occupy different niches when exploiting limited resources such as water and nutrients. I investigated two competition-based models, each of them considering a different axis for niche separation: the two-layer hypothesis, which is based on differences in rooting depth, and the phenological niche separation hypothesis, which is based on differences in timing of resource acquisition. My results show that niche separation along environmental axes on spatial and/or temporal scales, although unlikely to be the only mechanism of coexistence in savannas, may play a more significant role than has been appreciated recently.